2017
DOI: 10.3390/ijerph14060628
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Low Health Literacy: A Community-Based Study in Shanghai, China

Abstract: Background: Health literacy is an increasingly important public health concern. However, little is known about the health literacy of general public in China. The aim of this study was to evaluate the prevalence of low health literacy and demographic associations in Shanghai, China. Methods: This study was a community-based cross-sectional health survey utilizing a multi-stage random sampling design. The sample consisted of 1360 individuals aged 15–69 years with the total community-dwelling Chinese as the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
68
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 17 publications
(20 reference statements)
9
68
1
Order By: Relevance
“…Previous studies reported similar findings. [25][26][27] In addition, Sun et al, reported that education has a positive and direct effect on prior knowledge and health literacy. 28 This should help the policy of focusing on promoting health literacy and integrating the education of knowledge of specific diseases in the school curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported similar findings. [25][26][27] In addition, Sun et al, reported that education has a positive and direct effect on prior knowledge and health literacy. 28 This should help the policy of focusing on promoting health literacy and integrating the education of knowledge of specific diseases in the school curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the Institute of Medicine (IOM) de nes health literacy as "An individual's ability to access, process, and understand basic health information and services needed to make sound health-related decisions and follow treatment guidelines." This study used the de nition given by the World Health Organization, i.e., the extent to which individuals have the cognitive and social skills necessary to obtain, understand and apply basic health information and services to promote and maintain good health [3][4] . Today, health literacy remains inadequate in many countries and regions, especially among the most vulnerable socioeconomic groups [5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
“…21 The significantly higher levels of inadequate HL in the sample from China is consistent with research demonstrating elevated levels of inadequate HL in this population. 22 While China has undergone rapid economic development, changes in levels of basic and HL have not kept pace, particularly in rural areas and urban areas with low income. The high levels of inadequate HL is likely to present challenges to maintaining adequate healthcare and reducing mortality and morbidity from chronic illnesses in a large, aging population.…”
Section: Discussionmentioning
confidence: 99%